Policy lessons from Ireland's latest depression - Karl Whelan (University College Dublin, UCD School of Economics, 2009)
In this paper, I provide a selective review of Ireland's economic performance of the last 20 years, from the early days of the Celtic Tiger, through to the housing boom and the recent slump, and then attempt to draw a few lessons from the period. I argue, based on a range of observations, that a substantial slowdown was looming for Ireland by 2007, independent of what was going to happen in the global economy, and much of this evidence was ignored in the implementation of economic policy. The result was a range of policies based on an unwarranted over-optimism which left Ireland terribly exposed to the international downturn. Policy failures in the fiscal and banking are are discussed, as well as some common criticisms of policy that have less justification.
hdl:10197/2612
Keywords: 330